Kepemilikan Jamban Sehat Pada Masyarakat - Mukhlasin Mukhlasin; Encep Nugraha Solihudin (Universitas Faletehan, 2020)
The use of gooseneck latrines among the community of Walikukun Village, Carenang District, Serang Regency achieves 50.36%, users. The purpose of this study is to determine the availability of clean water, land availability, and income associated with latrine ownership among the community of Walikukun Village, Carenang District, Serang Regency in 2020. The method of this study is cross-sectional design. The number of respondents in this study are 87 respondents. The sampling technique used simple random sampling and the bivariate analysis used Chi square test. The results showed that all variables were related to latrine ownership in Walikukun Village, Carenang District, Serang Regency; availability of clean water (p value 0.000; OR 117.818), land availability variable (p value 0.000), income variable (p value 0.000). The conclusion of this study is that some people (68.8%) did not have a toilet.